2014
DOI: 10.1007/s12031-014-0371-y
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid 2-Arachidonylglycerol Protects Primary Cultured Neurons Against Homocysteine-Induced Impairments in Rat Caudate Nucleus Through CB1 Receptor

Abstract: Homocysteine (Hcy) is a high risk factor for Alzheimer's disease (AD). Caudate nucleus (CN), the major component of basal ganglia in the brain, is also involved in many neurological disorders. 2-Arachidonoylglycerol (2-AG), the true natural ligand for cannabinoid type-1 (CB1) receptors and the most abundant endogenous cannabinoid, has been shown to exhibit neuroprotective effects through its anti-inflammatory action from proinflammatory stimuli in the hippocampus and CN. However, it is still not well understoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 51 publications
4
9
0
Order By: Relevance
“…URB602 inhibits the phosphorylation of NF-κB and degradation of IκB-α in response to Hcy in the primary CN neurons via the CB1 receptor A preceding study showed that the NF-κB signaling pathway was involved in the lipopolysaccharide (LPS)-induced or Hcy-induced neuroinflammation in the hippocampus and CN [14,25,40,41]. To determine whether this signaling pathway is involved in the URB602 suppression of COX-2 induced by Hcy in the CN neurons, we detected the phosphorylation level of NF-κB in the CN neurons.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…URB602 inhibits the phosphorylation of NF-κB and degradation of IκB-α in response to Hcy in the primary CN neurons via the CB1 receptor A preceding study showed that the NF-κB signaling pathway was involved in the lipopolysaccharide (LPS)-induced or Hcy-induced neuroinflammation in the hippocampus and CN [14,25,40,41]. To determine whether this signaling pathway is involved in the URB602 suppression of COX-2 induced by Hcy in the CN neurons, we detected the phosphorylation level of NF-κB in the CN neurons.…”
Section: Resultsmentioning
confidence: 99%
“…In the hippocampus and CN, mitogen-activated protein kinase (MAPK) ERK1/2 is also known to be involved in the antiinflammatory properties of eCBs [12,14,25,40,41]. Therefore, we tested the level of phospho-ERK1/2 (p-ERK1/2) by Western blot.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations